2020
DOI: 10.1111/bdi.12994
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of rapid cycling bipolar patients presenting with major depressive episode within the BRIDGE‐II‐MIX study

Abstract: BRIDGE-II-Mix) study aimed to estimate the frequency of mixed states in patients with a major depressive episode (MDE) according to different definitions and to compare their clinical validity, looking into specific features such as rapid cycling (RC).Methods: Psychiatric symptoms, socio-demographic, and clinical variables were collected from a sample of 2811 MDE patients, of which 726 (25.8%) were diagnosed with bipolar disorder (BD). The characteristics of bipolar patients with RC (BD-RC) and without (BD-NRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 80 publications
1
4
0
Order By: Relevance
“…However, consistent with previous observations, there were significant and selectively higher rates of depressions/year with BD2, with a trend toward fewer episodes of mood-elevation and a greater risk of rapid cycling 5,48,58,59,68,85–87 . It is also noteworthy that rapid cycling has had more association with depression than with recurrence of [hypo]mania, perhaps particularly with BD2 86,88–90 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, consistent with previous observations, there were significant and selectively higher rates of depressions/year with BD2, with a trend toward fewer episodes of mood-elevation and a greater risk of rapid cycling 5,48,58,59,68,85–87 . It is also noteworthy that rapid cycling has had more association with depression than with recurrence of [hypo]mania, perhaps particularly with BD2 86,88–90 …”
Section: Discussionsupporting
confidence: 89%
“…5,48,58,59,68,[85][86][87] It is also noteworthy that rapid cycling has had more association with depression than with recurrence of [hypo]mania, perhaps particularly with BD2. 86,[88][89][90] Additionally, there were some shared demographic variables among similar BD2 and BD1 subjects, including marital status and level of education; although, risk of unemployment was 1.19-times greater with BD1 (Table 1). Other studies have found higher rates of marital separation and divorce and fewer years of education in BD1 vs. BD2 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid cycling (RC) affects up to 33% of bipolar patients 15 and is associated with worse outcomes of the mood disorder, greater comorbidity and polypharmacy. 16 Data concerning the pharmacological treatment of RC patients are scant and in several instances conflicting. Lithium, valproate, quetiapine, and olanzapine seem to have comparable – but poor – maintenance properties for RC patients while some evidence supports the use of lamotrigine in RC BD type II but not type I.…”
Section: Casementioning
confidence: 99%
“…RCBD patients predominantly experience frequent depressive episodes and atypical features and are often diagnosed with bipolar II disorder (BD-II) (Miola et al 2023a ; Kupka et al 2003 ). This subtype is characterized by an earlier onset, a prolonged course of illness, and increased psychiatric comorbidities (Carvalho et al 2014 ; Miola et al 2023a ; Valentí et al 2015 ; Kato et al 2020 ; Takano et al 2023 ; Antonietta Furio et al 2021 ; Yao et al 2023 ; Prisciandaro et al 2019 ), often coupled with increased substance and alcohol abuse(Carvalho et al 2014 ; Gordon-Smith et al 2020 ), and adverse childhood experiences(Miola et al 2023a , 2023b ; Yao et al 2023 ). Clinically, RCBD presents with greater disease severity, increased suicide attempts(Carvalho et al 2014 ; Miola et al 2023a , 2023b ; Valentí et al 2015 ; Takano et al 2023 ), and a higher risk of recurrence and hospitalization(Kato et al 2020 ; Miola et al 2023b ; Sengupta and Jena 2022 ).…”
Section: Introductionmentioning
confidence: 99%